(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores Yusuf Khos Hajib’s Kutadgu Bilig, highlighting its insights into educational and moral perspectives. The work examines the role of moral and pedagogical principles in fostering students’ moral development.